Socioeconomic inequalities in frailty among older adults in six low- and middle-income countries: Results from the WHO Study on global AGEing and adult health (SAGE). (September 2018) - Hoogendijk, Emiel O.; Rijnhart, Judith J.M.; Kowal, Paul; Pérez-Zepeda, Mario U.; Cesari, Matteo; Abizanda, Pedro; Flores Ruano, Teresa; Schop-Etman, Astrid; Huisman, Martijn; Dent, Elsa
Highlights: Studies of socioeconomic health inequalities in low- and middle-income countries (LMICs) are relatively scarce. This study investigated socioeconomic inequalities in frailty among older adults in six LMICs. Substantial socioeconomic inequalities in frailty were observed among older adults in LMICs. Chronic diseases did not explain the higher prevalence of frailty in lower socioeconomic groups. These findings may have implications for preventive strategies aimed at reducing frailty in LMICs. Abstract: Objectives: The aim of this study was to investigate socioeconomic inequalities in frailty among older adults in six low- and middle-income countries (LMICs), and to examine to what extent chronic diseases account for these inequalities. Study design: Data were used from the Study on global AGEing and adult health (SAGE) wave 1 (2007–2010). Nationally representative samples of adults aged 50+ years from China, Ghana, India, Mexico, the Russian Federation and South Africa were analyzed (n = 31, 174). Main outcome measures: Educational level and wealth were used as socioeconomic indicators. Frailty was assessed with modified criteria for the frailty phenotype. Self-reported disease diagnoses were used. A relative index of inequality (RII) was calculated to compare socioeconomic inequalities in frailty between countries. Results: People in lower socioeconomic positions had higher prevalence rates of frailty. The largest inequalities in frailty were found in Mexico (RII 3.7, 95% CI 2.1–6.4), and the smallest inequalities in Ghana (RII 1.1, 95% CI 0.7–1.8). Mediation analyses revealed that the chronic diseases considered in this study do not explain the higher prevalence of frailty seen in lower socioeconomic groups. Conclusions: Substantial socioeconomic inequalities in frailty were observed in LMICs, but additional research is needed to find explanations for these. Given that the population of older adults in many LMICs is expanding at a greater rate than in many high-income countries, our results indicate an urgent public health need to address frailty in these countries.